2020
DOI: 10.1016/j.abrep.2020.100308
|View full text |Cite
|
Sign up to set email alerts
|

Deter the emotions: Alexithymia, impulsivity and their relationship to binge drinking

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 80 publications
2
16
0
Order By: Relevance
“…This Special Issue gathers 11 original research and review articles that address different types of binge behaviors: binge drinking ( Deniel et al, 2021 , Gierski et al, 2020 , Herman et al, 2020 , Mange et al, 2021 , Werle et al, 2021 ), binge eating ( Prunell-Castañé et al, 2021 , Werle et al, 2021 ), binge watching ( Cordeiro et al, 2021 , Ort et al, 2021 , Rubenking and Bracken, 2021 , Werle et al, 2021 ), and binge-porn consumption (i.e., hypersexuality and problematic pornography use; Castro-Calvo et al, 2021 , Koós et al, 2021 ). These articles primarily consist of empirical studies that build on self-report questionnaires, but a few rely on behavioral assessments, ecological approaches (i.e., sampling experiences), or literature reviews.…”
Section: Summary Of the Current Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue gathers 11 original research and review articles that address different types of binge behaviors: binge drinking ( Deniel et al, 2021 , Gierski et al, 2020 , Herman et al, 2020 , Mange et al, 2021 , Werle et al, 2021 ), binge eating ( Prunell-Castañé et al, 2021 , Werle et al, 2021 ), binge watching ( Cordeiro et al, 2021 , Ort et al, 2021 , Rubenking and Bracken, 2021 , Werle et al, 2021 ), and binge-porn consumption (i.e., hypersexuality and problematic pornography use; Castro-Calvo et al, 2021 , Koós et al, 2021 ). These articles primarily consist of empirical studies that build on self-report questionnaires, but a few rely on behavioral assessments, ecological approaches (i.e., sampling experiences), or literature reviews.…”
Section: Summary Of the Current Special Issuementioning
confidence: 99%
“…Through dominance analysis, Mange et al (2021) demonstrate that binge drinking appears to be mainly determined by enhancement motives and drinking identity, followed by subjective norm and social motives, thus calling for the focus of attention to be placed on interindividual psychological factors for the sake of elaborating prevention strategies. Other potential targets for prevention and intervention are also suggested by Herman et al (2020) , who highlight the combined role of difficulties in emotion processing (i.e., alexithymia) and trait impulsivity in binge drinking among university students. Three review articles then provide an updated overview on cognitive impairments associated with binge behaviors.…”
Section: Summary Of the Current Special Issuementioning
confidence: 99%
“…A 2011 study (see [75]) showed a relationship between the DRD2 polymorphism (rs 1800497) and the development of alexithymia, which is associated with difficulties in awareness and self-regulation of emotions [75,78,79] and it seems that this trait could be related to the personality trait studied by us, which is "self-directed, including selfacceptance". People with alexithymia have less activation of "anterior cingulate cortex (ACC)", and thus process emotional stimuli differently [78,[80][81][82].…”
Section: Study Limitationsmentioning
confidence: 89%
“…Alexithymia is characterized by disturbances in emotional regulation (33). Alexithymia is a psychological trait, not only is there Di culty in Emotion Regulation, but there is also a defect in the cognitive processing of emotions, so emotions remain indistinguishable (29,30,34,35). Lan (36) states about people with Alexithymia that these people express emotional distress through physical complaints (35).…”
Section: Introductionmentioning
confidence: 99%
“…Alexithymia is a psychological trait, not only is there Di culty in Emotion Regulation, but there is also a defect in the cognitive processing of emotions, so emotions remain indistinguishable (29,30,34,35). Lan (36) states about people with Alexithymia that these people express emotional distress through physical complaints (35). Which is characterized by di culties in identifying and describing their emotional state and is associated with de cits in empathy and emotional awareness.…”
Section: Introductionmentioning
confidence: 99%